Benjamin F. Butler papers - Butler, Benjamin F. (Benjamin Franklin), 1818-1893.
Correspondence, letterbooks, order books, reports, notebooks, newspaper clippings, charts, maps, photographs, and other papers concerning Butler's Civil War commands, service as U.S. representative from and governor of Massachusetts, and candidacy for U.S. president in 1884. Documents Butler's participation in military operations in Maryland, 1861; Fort Clark and Fort Hatteras, Outer Banks, N.C., 1861; Petersburg, Va., 1864-1865; and Fort Fisher, N.C., 1864-1865. Also documents his service as military governor of New Orleans, La.; his activities as chairman of the congressional committee in 1867 investigating the assassination of Abraham Lincoln and as manager of the impeachment proceedings against President Andrew Johnson; and his career as a lawyer. Includes material pertaining to cases such as Ex parte Milligan (Lambdin P. Milligan) and United States v. Farragut (David Glasgow Farragut). Also includes Pinkerton's National Detective Agency reports and other files concerning the breach of promise case, Oliver v. Cameron (Mary S. Oliver and Simon Cameron).
Includes a letter with a detailed account from Charles Augustus Leale, a surgeon who witness Lincoln's assassination at Ford's Theatre and remained with him until his death; and correspondence with French and Spanish consuls in New Orleans and Butler's wife, Sarah Butler.
Library of Congress Geography and Map Division.
Army officer, state legislator and U.S. representative from Massachusetts, governor of Massachusetts, and military governor of New Orleans.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Card index to a portion of the correspondence available in the Library of Congress Manuscript Reading Room.
Keywords: Butler, Sarah Hildreth, -- 1816-1876 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Trials, litigation, etc; Farragut, David Glasgow, -- 1801-1870 -- Trials, litigation, etc; Johnson, Andrew, -- 1808-1875 -- Impeachment; Lincoln, Abraham, -- 1809-1865 -- Assassination; Milligan, Lambdin P. -- Trials, litigation, etc; Oliver, Mary S. -- Trials, litigation, etc; Pinkerton's National Detective Agency; Breach of promise; Consuls -- France -- Correspondence; Consuls -- Spain -- Correspondence; Habeas corpus -- United States; Martial law -- United States; Trials (Conspiracy) -- Indiana -- Indianapolis; Fort Fisher (N.C. : Fort) -- Siege, 1864-1865.; Louisiana -- History -- Civil War, 1861-1865.; Maryland -- History -- Civil War, 1861-1865.; Massachusetts -- Politics and government -- 19th century; New Orleans (La.) -- History -- Civil War, 1861-1865.; North Carolina -- History -- Civil War, 1861-1865.; Outer Banks (N.C.) -- History -- Civil War, 1861-1865.; Petersburg (Va.) -- History -- Siege, 1864-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Claims; United States -- Politics and government -- 1865-1900.; Virginia -- History -- Civil War, 1861-1865.; Army officers; Governors -- Massachusetts; Legislators -- Massachusetts; Military governors -- Louisiana -- New Orleans; Representatives, U.S. Congress -- Massachusetts